(untitled) (UNIZIK Journal of STM Education, 2023)
In Gombe State, achievement of students in Mathematics in WASSCE had been consistently unsatisfactory based on WAEC Chief Examiners’ Report in 2020, 2021 2022. This worrisome trend could probably be linked to the study habits of students in the subject. The purpose of the study was to ascertain the relationship between secondary school students’ study habit and their academic achievement in mathematics in Gombe State. Five research questions guided the study while three hypotheses were tested at 0.05 level of significance. Correlational research design was used for the study. The population of this study comprised all the 5, 161 (3, 343 males and 1818 females) Senior Secondary two (SS2) students in all the 71 government-owned secondary schools in Gombe North Education Zone. The sample of the study was made up of 1330 SS 2 students for the 2022/2023 academic session which was made up of 824 males and 506 females obtained via simple random sampling and proportionate sampling techniques. Study Habits Inventory (SHI) and students past annual records in mathematics promotion examination obtained from the sampled schools was used for data collection. The reliability of SHI was tested using Cronbach Alpha method. Coefficient value of 0.88 was obtained which was considered high enough to confirm the instrument as reliable. Data collected were analyzed using Pearson product moment correlation coefficients and t-test of correlation. The finding of the study indicated that a high positive and significant relationship existed between students` study habits and their achievement in Mathematics. Again, the findings of the study showed that across gender lines, a positive and significant relationship existed between students` study habits and their achievement in Mathematics. It was recommended among others that Mathematics teachers should evolve teaching strategies that will sustain students’ study habits inorder to enhance their academic achievement in Mathematics.